Allenamides as orthogonal handles for selective modification of cysteine in peptides and proteins - Abbas, Ata (2014)
In this study, a remarkably simple and direct strategy has been successfully developed to selectively label target cysteine residues in fully unprotected peptides and proteins. The strategy is based on the reaction between allenamides and the cysteine thiol, and proceeds swiftly in aqueous medium with excellent selectivity and quantitative conversion, thus forming a stable and irreversible conjugate. The combined simplicity and mildness of the process project allenamide as robust and versatile handles to target cysteines and has potential use in biological systems. Additionally, fluorescent-labeling studies demonstrated that the installation of a C-terminal allenamide moiety onto various molecules of interest may supply a new methodology towards the site-specific labeling of cysteine-containing proteins. Such a new labeling strategy may thus open a window for its application in the field of life sciences.